2021
DOI: 10.1158/1541-7786.mcr-20-0926
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Transferase – An Auxiliary Factor or a Full-blown Oncogene?

Abstract: The β-linked N-acetyl-D-glucosamine (GlcNAc) is a post-translational modification of serine and threonine residues catalyzed by the enzyme O-GlcNAc transferase (OGT). Increased OGT expression is a feature of most human cancers and inhibition of OGT decreases cancer cell proliferation. Anti-proliferative effects are attributed to post-translational modifications of known regulators of cancer cell proliferation, such as MYC, FOXM1 and EZH2. In general, OGT amplifies cell-specific phenotype, for example, OGT over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 141 publications
1
23
0
Order By: Relevance
“…7 ). Homeostasis of O - GlcNAc through activities of OGT and OGA has been previously implicated in normal hematopoietic development 96 , 97 , in differentiation arrest of AML and Jurkat T‑cells 98 as well as in other cancers 99 . However, our study is the first to report that this modification is also essential for the survival of MLL-r B-ALL cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Homeostasis of O - GlcNAc through activities of OGT and OGA has been previously implicated in normal hematopoietic development 96 , 97 , in differentiation arrest of AML and Jurkat T‑cells 98 as well as in other cancers 99 . However, our study is the first to report that this modification is also essential for the survival of MLL-r B-ALL cells.…”
Section: Discussionmentioning
confidence: 99%
“…OGT promotes protein O-GlcNAcylation ( 37 , 38 ) and has been found to be upregulated in most cancers including ESCC ( 39 , 40 ). In the present study, we found that total O-GlcNAcylation level is correlated with OGT expression and poor patient prognosis (R = 0.43, Figures 3F, G ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein O-GlcNAcylation is globally elevated in breast cancer and other malignancies that targets multiple transcription factors and alters gene expression pro les in the favour of metastatic and cancer stem cells [20,21,[29][30][31]. Therefore, cell stemness-related transcription factors were also included in our analysis in the context of their functions associated with high O-GlcNAc enrichment in tumors.…”
Section: Discussionmentioning
confidence: 99%